Derechos y ritos : iniciación y performatividad en el derecho y la educación jurídica - Yovel, Jonathan (2016)
This essay is about how language functions in law, and how prospective legal agents -young lawyers, law students- are initiated into a complex linguistic culture through various modes of instruction. Thus it confronts two approaches to legal education: one, which cuts across both lay and certain "professional" approaches to legal instruction, approaches law as a discipline, a body of knowledge to be mustered and mastered in the form of rules, precedents, policy arguments and the like. The other approaches legal practice and instruction as a complex linguistic culture, where the forms enumerated, rather than the "essence" of law, are offered as profitable to master because they tend to constitute the culture of communication of legal discourse, on top of being the kind of argumentation that is generally triumphant in the legal institutional context. However, before attempting to draw pedagogical insights, the bulk of this essay studies how notions of language use apply to legal performance. There are various ways to attempt such a study; the one employed here works through a nontechnical survey of some major approaches in the philosophy of language. Language springs from culture, practice and their historical dimensions, while law and legal instruction, ever since Hellenic times, were seen as paradigmatic contexts for the application and study of social language. Thus, the present inquiry will attempt to address the relations between language and action as a history of ideas centered on the following questions: What, as lawyers and speakers, do we do with words? What are the modes of language used in legal argumentation (and in litigation in particular)? How do we train and initiate prospective lawyers into a linguistic culture and ideology that underlie these questions? With no claim to exhaustiveness, this essay proposes to delineate, trace and reconstruct the main features of three interacting language functions significant in legal practice and theory: rhetoric, representationalism and performativity.